Economia abierta y desarrollo rural - Santiago C, M. de J.=700 1 Garcia D, G.
(Es, En)
Ilus., 15 ref.
Keywords: ANALISIS ECONOMICO; DESARROLLO RURAL; POLITICA ECONOMICA; ESTRUCTURA AGRICOLA; MEXICO; POLITICAS AGRICOLAS